Evolutionary and biologically inspired music, sound, art and design : 4th International Conference, EvoMUSART 2015, Copenhagen, Denmark, April 8-10, 2015, Proceedings /: 4th International Conference, EvoMUSART 2015, Copenhagen, Denmark, April 8-10, 2015, Proceedings. (2015) - Unknown
No abstract available